A core outcome set for resuscitative endovascular balloon occlusion of the aorta: A consensus based approach using a modified Delphi method. Issue 1 (January 2022) - Nahmias, Jeffry; Byerly, Saskya; Stein, Deborah; Haut, Elliott R.; Smith, Jason W.; Gelbard, Rondi; Ziesmann, Markus; Boltz, Melissa; Zarzaur, Ben; Biffl, Walter L.; Brenner, Megan; DuBose, Joseph; et al.
Abstract : BACKGROUND: The utilization of resuscitative endovascular balloon occlusion of the aorta (REBOA) in trauma has grown exponentially in recent years. However, inconsistency in reporting of outcome metrics related to this intervention has inhibited the development of evidence-based guidelines for REBOA application. This study sought to attain consensus on a core outcome set (COS) for REBOA. METHODS: A review of "landmark" REBOA articles was performed, and panelists (first and senior authors) were contacted for participation in a modified Delphi study. In round 1, panelists provided a list of potential core outcomes. In round 2, using a Likert scale (1 [not important] to 9 [very important]), panelists scored the importance of each potential outcome. Consensus for core outcomes was defined a priori as greater than 70% of scores receiving 7 to 9 and less than 15% of scores receiving 1 to 3. Feedback was provided after round 2, and a third round was performed to reevaluate variables not achieving consensus and allow a final "write-in" round by the experts. RESULTS: From 17 identified panelists, 12 participated. All panelists (12 of 12, 100%) participated in each subsequent round. Panelists initially identified 34 unique outcomes, with two outcomes later added upon write-in request after round 2. From 36 total potential outcomes, 20 achieved consensus as core outcomes, and this was endorsed by 100% of the participants. CONCLUSION: Panelists successfully achieved consensus on a COS for REBOA-related research. This REBOA-COS is recommended for all clinical trials related to REBOA and should help enable higher-quality study designs, valid aggregation of published data, and development of evidence-based practice management guidelines. LEVEL OF EVIDENCE: Diagnostic test or criteria, level V. Trial Registration: Core Outcomes in Trauma Surgery: Development of a Core Outcome Set for Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) http://www.comet-initiative.org/Studies/Details/1709 . Abstract : Supplemental digital content is available in the text.